Respons Antibodi Sekunder Terhadap Penyakit Tetelo pada Ayam Petelur Pascavaksinasi Ulangan dengan Vaksin Tetelo Aktif (NEWCASTLE DISEASESECONDARY ANTIBODY RESPONSE AFTER REVACCINATION IN LAYER WITH THE ACTIVE ND VACCINE) - Kurnianto, Andika Budi; Kencana, Gusti Ayu Yuniati; Astawa, I Nyoman Mantik (Jurnal Veteriner, 2016)
Revaccination is required in order to preventNewcastle Disease (ND) reccurence inlayers chickens. Oneof vaccine for ND revaccination is freeze-died ND active vaccine containing e” 106,5EID50. Revaccinationisdone to trigger a faster secondary antibody responses in layers and can achieve protective antibody titersagainst ND that can be monitored by a hemagglutinationinhibition (HI). The aim of this study was todetermine the ND secondary antibody responses in layers after revaccination with ND active vaccine.Antibody titer of 20 layers chickens of 20 week old were determined before revaccinations (week 0) andafter revaccinations (week 1 until week 9). The first vaccination was conducted using ND-IB (NewcastleDisease-Infectious Bronchitis) at the age of 2 days through eye drops and subcutaneous injection at the ageof 5 days using a dose of 1 ampoule.Vaccination is repeated at the age of 20 weeks at a dose of 1 ½ ampoule through drinking water. Blood samples were collected on the wing vein (venous cutane ulnar) and left for 5-10 minutes at room temperature.Sera were then collected and stored at -20oC until use. HI antibody titerwas determined by micro titeration system. The HI mean titers were analyzed by Duncan test. The studyresults showed that antibody titer before revaccination was3,47 HI log 2 and the HI titers after revaccinationwere 4,02; 5,22; 6,52; 7,85; 8,4; 8,6; 7,7; 5,92; dan 3,87 HI log 2 respectivelly at weeks 1, 2, 3, 4, 5, 6, 7, 8, and9.The NDV revaccination with ND active vaccine significantly (P <0.01) increased in antibody titer inlayers starting from week 1 to week 6, but decreased following week 7 to week-9. It can be concluded thatrevaccinantion with ND active vaccine increases the antibody titers in layer chickens.
Keywords: ND active vaccine; a secondary antibody response; revaccination; layers; serology